Extract From Plectranthus amboinicus Inhibit Maturation and Release of Interleukin 1β Through Inhibition of NF-κB Nuclear Translocation and NLRP3 Inflammasome Activation - Leu, Wohn-Jenn; Chen, Jui-Ching; Guh, Jih-Hwa (Frontiers in Pharmacology, 2019)
Uncontrolled inflammation may produce massive inflammatory cytokines, in which interleukin 1β (IL-1β) plays a key role, resulting in tissue damage and serious disorders. The activation of NLRP3 inflammasome is one of the major mechanisms in maturation and release of IL-1β. Plectranthus amboinicus is a perennial herb. Several pharmacological activities of natural components and crude extracts from Plectranthus amboinicus have been reported including anti-inflammation; however, the underlying mechanism is not clear. Phorbol-12-myristate 13-acetate-differentiated THP-1 monocytic leukemia cells were used as a reliable model in this study to examine the effect on inflammasome signaling pathway by PA-F4, an extract from Plectranthus amboinicus. PA-F4 inhibited ATP-induced release of caspase-1, IL-1β and IL-18 from LPS-primed cells. PA-F4 induced a concentration-dependent inhibition of both ASC dimerization and oligomerization in cells under LPS priming plus ATP stimulation. Co-immunoprecipitation of NLRP3 and ASC demonstrated that PA-F4 significantly blunted the interaction between NLRP3 and ASC. Furthermore, PA-F4 completely abolished ATP-induced K+ efflux reaction in LPS-primed cells. Taken together, PA-F4 displayed an inhibitory activity on NLRP3 inflammasome activation. Moreover, PA-F4 also inhibited LPS-induced p65 NF-κB activation, suggesting an inhibitory activity on LPS priming step. Further identification showed that rosmarinic acid, cirsimaritin, salvigenin and carvacrol, four constituents in PA-F4, inhibited LPS-induced IL-6 release. In contrast, rosmarinic acid, cirsimaritin and carvacrol but not salvigenin inhibited ATP-induced caspase-1 release from LPS-primed cells. In conclusion, PA-F4 displayed an inhibitory activity on activation of NLRP3 inflammasome. PA-F4 inhibited LPS priming step through block of p65 NF-κB activation. It also inhibited ATP-induced signaling pathways in LPS-primed cells including the inhibition of both ASC dimerization and oligomerization, K+ efflux reaction, and the release reaction of caspase-1, IL-1 and IL-18. Rosmarinic acid, cirsimaritin, salvigenin and carvacrol could partly explain PA-F4-mediated inhibitory activity on blocking the activation of NLRP3 inflammasome.